Surface bio-magnetism and its biophysical effects on bacterial cells - Chua, Loh You (2008)
A novel technique has been developed to influence bacterial adhesion, the subsequent formation of microbial biofilms, and the consequential effects on planktonic cell growth. This is achieved by using the properties of anisotropy surface energy and the phemomena of ordered electron spins to either channel the energy away or towards the open surfaces, which affects the biophysical interactions with the adhering bacteria.